Construction and analysis of an objective test in high school mathematics - Ocampo, Nenita S. Carale 1939- (1968)
This seminar paper aims to give some insights on test construction and the corresponding item analysis and interpretation of test result. In addition, the paper aims to trace the main areas in mathematics where students find difficulty and its implications to the teaching-learning process.
Vita.
Thesis (M.A.T. Mathematics)--University of the Philippines, Diliman.
Keywords: Examinations -- Design and construction; Examinations -- Interpretation; Objective tests -- Philippines -- Queson City; Mathematics -- Study and teaching (Secondary) -- Philippines -- Quezon City